Gummatous lesions in men infected with human immunodeficiency virus and syphilis. Issue 5 (October 1990) - Hay, P E; Tam, F W; Kitchen, V S; Horner, S; Bridger, J; Weber, J
Abstract : Two HIV-infected men are reported who developed gummatous lesions more than 12 months after appropriate treatment of presumptive syphilis. In one patient the lesions developed without any change in the VDRL titre. The most likely explanation for these lesions is reactivation of syphilis in the context of HIV infection. As these lesions respond to penicillin, the possible reactivation of appropriately treated syphilis, or even yaws, should now be considered in any ulcerative lesion in HIV infected individuals at risk from treponemal infection.